An analysis of speech errors of English as a second language learners in UiTM Negeri Sembilan / Norfazlika Abd. Karim - Abd. Karim, Norfazlika (Research Management Institute (RMI), 2013)
This study examined errors in the speech transcripts of 18 learners during their first semester Pre-Diploma in Science taking Pre-Diploma English I (BEL 021) course at Universiti Teknologi MARA, Negeri Sembi/an. The objectives of the study were to identify the speech errors and the possible sources ofsuch errors as some English as a Second Language (ESL) teachers seemed to make only few attempts in correcting errors in their evaluation ofthe learners' speaking tasks due to the fact that they might not be fully equipped with a practical guide to an examination of learners' spoken English errors. Data were obtained through the learners' individual oral presentation in which it was tape-recorded. transcribed and analysed for errors. An analysis of the speech errors suggested that the sources of errors may be attributable to two major transfers: interlingual and intralingual and most errors learners produce resulting from the normal development of the target language (intralingual errors).